Application of fluorescence microscopy for histological discrimination of golden camellias leaves - Van Anh, Le Thi; Phuong Nga, Mai Thi; Phuong Linh, Tran; Minh Anh, Nguyen; Phuong Linh, Huynh Thi; Chi Thanh, Nguyen; Thu Phuong, Le Thi; Kieu Oanh, Nguyen Thi (Vietnam Journal of Biotechnology, 2023)
Histological analysis, which aims to investigate the microscopic anatomy of biological tissues, has been a simple and powerful technique for plant taxonomy. Sectioning followed by staining methods is widely used in observing histological structures. However, the staining techniques often destroy tissue and provide low-quality images due to nonspecific reactions with the dyes making further analysis difficult. In this report, we propose an applicable non-staining histology protocol based on auto-fluorescence characteristics of plant tissues and its application in the anatomical discrimination of six similar-appearance species of golden camellias as a case study. We compared the images from the same tissue under a bright field with the staining step and under fluorescence directly without the staining step in the sample preparation. The images were taken from Eclipse Ni-U microscopy (Nikon, Japan) with a color DS-Ri2 camera (Nikon, Japan) and NIS-ELEMENTS Basic Research Imaging software. The non-staining method demonstrated significant advantages compared to the staining protocol. The fluorescent images showed the distinction between adjacent leaf tissues with their own naturally reflective colors. In addition, the anatomical parameters, including the xylem area, phloem area, bundle sheath area, and palisade/spongy width ratio, were easily measured in good-quality images. These parameters were used in discriminative analysis by the Principal Component Analysis (PCA). The PCA diagram demonstrated the separation of six species, thus suggesting that these anatomical parameters can be used for taxonomy. In conclusion, our study showed a helpful technique in histological analysis that significantly contributes to the taxonomy of golden camellias species and can be applied in other plant varieties.